Quasi-static shear-compression tests on stone masonry walls with plaster: Influence of load history and axial load ratio. (1st August 2019) - Godio, Michele; Vanin, Francesco; Zhang, Shenghan; Beyer, Katrin
Highlights: The wall stiffness increases with increasing axial load ratio. The wall force capacity increases with increasing axial load ratio. The ultimate drift and drift capacity decrease with increasing axial load ratio. The load history has negligible influence on the wall stiffness and force capacity. The wall drift capacity decreases with increasing number of cycles per drift demand. Abstract: This paper describes quasi-static cyclic shear-compression tests on six plastered single-leaf stone masonry walls. Of the six walls, four are tested under different axial load ratios, performing a cyclic load history with two cycles per increasing drift demand. Three are tested under the same axial load ratio but are subjected to different load histories, namely, one monotonic loading, one cyclic loading with two cycles per drift level and one cyclic loading with one hundred cycles per drift level. Stiffness, force capacity and drift measures corresponding to six different limit states of the walls are extracted from each test and the effect of the axial load ratio and of the load history on these parameters is investigated. Changing the axial load ratio on the tested walls confirms findings from previous studies, according to which, with increasing axial load the wall stiffness and the force capacity increase while the ultimate drift decreases. Varying the number of cycles in the applied load history brings new findings, showing that all the drift measures of the walls, especially those corresponding to limit states attained in the post-peak regime, are very sensitive to the number of cycles applied while the stiffness and the force capacity are not. These trends are shown in the paper and compared against code and literature provisions for in-plane loaded walls. One face of each wall is plastered and the damage of the plaster is compared to the damage of the stone and mortar. This information is required when assessing the non-structural damage of the walls.